2018
DOI: 10.1080/09500693.2018.1477261
|View full text |Cite
|
Sign up to set email alerts
|

Multilingual students’ use of translanguaging in science classrooms

Abstract: This study describes multilingual students' authentic use of their first and second languages in a translanguaging science classroom, from a sociocultural perspective. The study is ethnographic, and has followed some lessons each month in a translanguaging science classroom at a primary school for three years. The observed lessons were documented by four video cameras and four audio recorders, while field notes and different types of students' texts and other teaching materials were also collected. In order in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 41 publications
3
44
0
5
Order By: Relevance
“…This implies that the students' discursive mobility (Nygård Larsson 2011), their ability to move between discourses, increases when they use both Swedish and Arabic. Moreover, analyses show how the students often use both Swedish and Arabic to clarify semantic relationships between scientific words and concepts in this practice (Karlsson et al 2018). The students commonly express the subject-specific words in Swedish, while the descriptive, clarifying, interconnecting words and phrases describing the semantic relationships often are expressed in Arabic.…”
Section: Verbal Language Usage In a Translanguaging Science Classroommentioning
confidence: 99%
See 3 more Smart Citations
“…This implies that the students' discursive mobility (Nygård Larsson 2011), their ability to move between discourses, increases when they use both Swedish and Arabic. Moreover, analyses show how the students often use both Swedish and Arabic to clarify semantic relationships between scientific words and concepts in this practice (Karlsson et al 2018). The students commonly express the subject-specific words in Swedish, while the descriptive, clarifying, interconnecting words and phrases describing the semantic relationships often are expressed in Arabic.…”
Section: Verbal Language Usage In a Translanguaging Science Classroommentioning
confidence: 99%
“…A translanguaging practice is a space for teaching and learning through multimodal interactions and semiotic inter-relationships (such as oral and written language, signs, gestures and symbols). According to Karlsson et al (2018), a translanguaging science classroom constitutes a third space in science education, in which students and teachers can use all available languages resources in a pragmatic and functional way to relate the science subject matter to prior experience in all meaning-making processes. In this way, third spaces in science education can be important for continuity in science learning for those students who have limited opportunities to understand and express themselves in the language of instruction.…”
Section: Meeting Place For Both Discursive and National Languagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Palmer, Martínez, Mateus, and Henderson () found that two bilingual teachers modeled translanguaging and celebrated it as a resource for academic content learning. In a study of a public school science classroom, Karlsson, Larsson, and Jakobsson () found that translanguaging promoted students’ abilities to relate to the science content and contextualize it within relevant areas of knowledge. Translanguaging is gaining attention in linguistics circles, but it has not become a part of mainstream science education conversations or professional development initiatives yet.…”
Section: Literature Reviewmentioning
confidence: 99%